Practical Microsoft Azure IaaS Migrating and Building Scalable and Secure Cloud Solutions - Ambi Karthikeyan, Shijimol (Apress, 2018)
Adopt Azure IaaS and migrate your on-premise infrastructure partially or fully to Azure. This book provides practical solutions by following Microsoft's design and best practice guidelines for building highly available, scalable, and secure solution stacks using Microsoft Azure IaaS. The author starts by giving an overview of Azure IaaS and its components: you'll see the new aspects of Azure Resource Manager, storage in IaaS, and Azure networking. As such, you'll cover design considerations for migration and implementation of infrastructure services, giving you practical skills to apply to your own projects. The next part of the book takes you through the different components of Azure IaaS that need to be included in a resilient architecture and how to set up a highly available infrastructure in Azure. The author focuses on the tools available for Azure IaaS automated provisioning and the different performance monitoring and fine-tuning options available for the platform. Finally, you'll gain practical skills in Azure security and implementing Azure architectures. After reading Practical Microsoft Azure IaaS, you will have learned how to map the familiar on-premise architecture components to their cloud infrastructure counterparts. This book provides a focused and practical approach to designing solutions to be hosted in Azure IaaS. You will: Map the key Azure components to familiar concepts in infrastructure, such as virtualization, storage provisioning, switching, and firewalls Implement Azure IaaS deployment architectures Design IaaS environments in line with the Microsoft recommended best practices for scalability, resiliency, availability, performance, and security Manage the operational aspects of hosted environments, leverage automation, and fine tune for optimal performance.